Open and transparent budget process in Western Balkan Countries - Nikolov, Marjan; Trenovski, Borce; Dimovska, Gabriela (Center for Economic Analyses, 2015)
Budget openness and transparency are key elements of the effective management of public finances, determining the fiscal risks, rational financial decision-making, increasing accountability by policy makers and improving fiscal policies. It is difficult to define budget transparency, and also its measurement is an exceptional challenge. This is because different researchers/institutions use different ways (mostly questionnaires or surveys) to measure the fiscal transparency. Our research is mainly focused on elaborating the openness of budget processes in Western Balkan countries (as a specific group of countries consisted of: Albania, Bosnia and Herzegovina, Montenegro, Macedonia, Kosovo and Serbia) dominantly based on a globally accepted methodology designed by Open Budget Partnership (Open Budget Index and Open Budget Survey Tracker), and partly on our own analysis.
Keywords: budget transparency, Western Balkans, open budget index